Experimental Study of the Creep Effect on the Mechanical Properties of Concrete - Zainab Kammouna; Matthieu Briffaut; Yann Malecot (Advances in Civil Engineering)
Available researches regarding the effect of a sustained load on concrete are limited and sometimes contradictory. In the specific context of prestressed concrete and more generally for all other concrete structures, the effect of creep on the residual mechanical properties of concrete must be closely studied in order to accurately estimate the residual load capacity of a structure. In this study, therefore, sealed concrete specimens were subjected to sustained compressive and tensile loads; then, at the end of each creep test, the mechanical properties were investigated. Results revealed that when applied at a young age (1 month), the compressive creep load leads to an improvement in both compressive strength and elastic modulus. Conversely, when the load is applied at a later age (3 months), the creep strain acts to lower strength while it has almost no effect on the elastic modulus. The tensile creep was also studied for a single loading age (1 month); creep at this low loading level was found to increase tensile strength yet exerted a negligible visible effect when applied at a high loading level. Hence, the most important conclusion of this study is that the effect of creep on mechanical properties of concrete strongly depends on both loading age and loading direction.